(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2009)
Carcinoma of the cervix is a preventable female malignancy. Recently, a 30 years old 5th gravid lady was referred to Bangabandhu Sheikh Mujib Medical University (BSMMU) from Jahurul Islam Medical College & Hospital, Bajitpur, Kishorganj after diagnosing as a case of 32 weeks pregnancy coupled with invasive carcinoma of the cervix. Histopathology of cervical tissue showed moderately differentiated squamous cell carcinoma. Her cervical growth was confined in the anterior lip of the cervix and clinical stage was 1B. She was severely anemic. Her anemia had been corrected by blood transfusion. Injection dexamethasone was given for fetal lung maturity. Renal function tests and all other investigations for surgical fitness were done. At her 34th weeks of pregnancy caesarean section followed by Wertheim’s hysterectomy was performed. Baby was alive, birth weight was 2.3 kg, Apgar score was good. Postoperative period was un-event full. At her 23rd postoperative day she was discharged from Obs and Gynae department and referred to Oncology institute for further management. At the time of discharge her baby was healthy. Key Words: Cervical cancer, pregnancy, Wertheim’s hysterectomy. DOI: 10.3329/bsmmuj.v2i1.3712 BSMMU J 2009; 2(1): 47-49